The effects of weight loss and improved metabolic health status on the risk of non-alcoholic fatty liver disease—results from a prospective cohort in China - Huang, Xin; Ouyang, Wenbin; Hu, Yang; Tang, Bei; He, Yongmei; Wu, Hao; Yang, Pingting; Yin, Lu; Liu, Qingqi; Chen, Kui; Deng, Jing; Li, Xiaohui; et al. (Frontiers in Nutrition, 2023)
Background: The impact of weight loss and/or improved metabolic status on the risk of NAFLD (nonalcoholic fatty liver disease) has yet to be determined. Methods: A total of 35,322 participants without NAFLD were followed. NAFLD risk was compared between consistently MHNO (metabolically healthy non-obese) and non-MHNO who lost weight to become non-obese and/or improved their metabolic health, using Cox proportional hazards and Logistic regression models. Results: Following for 148,186 person-years, 8,409 participants had onset NAFLD, with an incidence rate of 56.75 (95% CI: 55.57, 57.94) per 1,000 person-years. MHO (metabolically healthy obese), MUO (metabolically unhealthy obese) and MUNO (metabolically unhealthy non-obese) at baseline were associated with increased NAFLD risk, with hazard ratios of 4.48 (95%CI:4.24, 4.73), 8.85 (95%CI:7.95, 9.84), and 10.70 (95%CI:9.73, 11.78). Weight loss and/or metabolic status improvements could significantly reduce NAFLD risk by 79.46% to 41.46%. Specifically, after weight loss from MHO to MHNO, the reduction in NAFLD risk (OR decreased from 12.01 (95%CI:9.40, 15.35) to 4.14 (95%CI:3.08, 5.57)) was greater than that of the MUNO subgroup whose metabolic status improved to MHNO (OR decreased from 5.53 (95%CI:5.15, 5.94) to 2.71 (95%CI:2.50, 3.93)). In the MUO subgroup, the group with the greatest risk reduction of NAFLD was the weight and metabolic state both improvement group (MUO to MHNO, OR decreased from 22.74 (95%CI:17.61, 29.37) to 4.67 (95%CI:3.05, 7.16)), followed by the weight loss only group (MUO to MUNO, OR decreased to 6.83 (95%CI:4.87, 9.57)), and finally the group with the least and insignificant risk reduction was the metabolic state improvement group (MUO to MHO, OR decreased to 13.38 (95%CI:9.17,19.53)). NAFLD risk was negatively correlated with the duration of improvement (P<0.001). Conclusions: Individuals with non-MHNO were more likely to develop NAFLD than those with consistent MHNO, but metabolic improvements and weight loss can alleviate the risk. Their NAFLD risk was negatively correlated with improvement duration. However, it remained higher than in individuals with consistent MHNO at an average follow-up of 4.2 years. Keywords: obesity, metabolic health, NAFLD, cohort study, loss weight